Edukasi Pola Hidup Sehat Pada Masyarakat Desa Daleman Dalam Upaya Mewujudkan Desa Bebas Stunting - Setiani, Dyah Arum; Zai, Titus Trison; Andrijati, Noening (Jurnal Bina Desa, 2025)
The community service aimed to increase awareness of healthy lifestyles in the Daleman Village community in order to achieve stunting-free village status. The service method is education to teenagers and socialization of a healthy, balanced menu. The activity partners were youth representatives from each RT in Daleman Village and students of SDN 2 Daleman. The results of service activities show increased understanding of nutrition, diet and the role of exercise in preventing stunting. By understanding the local context, this program aims to make a positive contribution to improving the health and nutritional needs of children in Daleman Village.